Methane in shallow subsurface sediments at the landward limit of the gas hydrate stability zone offshore western Svalbard. (1st February 2017) - Graves, Carolyn A.; James, Rachael H.; Sapart, Célia Julia; Stott, Andrew W.; Wright, Ian C.; Berndt, Christian; Westbrook, Graham K.; Connelly, Douglas P.
Abstract: Offshore western Svalbard plumes of gas bubbles rise from the seafloor at the landward limit of the gas hydrate stability zone (LLGHSZ; ∼400 m water depth). It is hypothesized that this methane may, in part, come from dissociation of gas hydrate in the underlying sediments in response to recent warming of ocean bottom waters. To evaluate the potential role of gas hydrate in the supply of methane to the shallow subsurface sediments, and the role of anaerobic oxidation in regulating methane fluxes across the sediment–seawater interface, we have characterised the chemical and isotopic compositions of the gases and sediment pore waters. The molecular and isotopic signatures of gas in the bubble plumes (C1 /C2+  = 1 × 10 4 ; δ 13 C-CH4  = −55 to −51‰; δD-CH4  = −187 to −184‰) are similar to gas hydrate recovered from within sediments ∼30 km away from the LLGHSZ. Modelling of pore water sulphate profiles indicates that subsurface methane fluxes are largely at steady state in the vicinity of the LLGHSZ, providing no evidence for any recent change in methane supply due to gas hydrate dissociation. However, at greater water depths, within the GHSZ, there is some evidence that the supply of methane to the shallow sediments has recently increased, which is consistent with downslope retreat of the GHSZ due to bottom water warming although other explanations are possible. We estimate that the upward diffusive methane flux into shallow subsurface sediments close to the LLGHSZ is 30, 550 mmol m −2  yr −1, but it is <20 mmol m −2  yr −1 in sediments further away from the seafloor bubble plumes. While anaerobic oxidation within the sediments prevents significant transport of dissolved methane into ocean bottom waters this amounts to less than 10% of the total methane flux (dissolved + gas) into the shallow subsurface sediments, most of which escapes AOM as it is transported in the gas phase.